MO009: Creatine-Kinase Elevation in Autosomal Dominant Polycystic Kidney Disease Patients on Tolvaptan Treatment. (3rd May 2022) - Rodríguez Espinosa, Diana; Jesus Broseta Monzo, Jose; Cuadrado, Elena; Fernando Quintana Porras, Luis; Poch, Esteban; Piñeiro, Gaston; Agraz, Irene; Sánchez-Baya, Maya; Furlano, Monica; Ruiz, César; Torra, Roser; Blasco, Miquel
Abstract: BACKGROUND AND AIMS: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary cause of end-stage kidney disease. Currently, tolvaptan is the only treatment that has proven to delay disease progression. The most notable side-effect of this therapy is drug-induced liver injury; however, recently, there have been two reports of creatine kinase (CK) elevation in ADPKD patients on tolvaptan treatment. We set out to monitor and determine the actual incidence of CK elevation and evaluate its potential association with other clinical factors. METHOD: This is an observational prospective multicenter study performed in rapidly progressive ADPKD patients on tolvaptan treatment from Barcelona, Spain. Laboratory tests, demographics, treatment dose and reported symptoms were collected from October 2018 to March 2021. RESULTS: Ninety-five patients initiated tolvaptan treatment during follow-up. The medication had to be discontinued in 31 (32.6%) patients, primarily due to aquaretic effects (12.6%), elevated liver enzymes (8.4%) and symptomatic or persistently elevated CK levels (3.2%). Moreover, a total of 27 (28.4%) patients elevated CK levels, with most of them being either transient (12.6%), mild and asymptomatic (4.2%), or resolved after dose reduction (3.2%) or temporary discontinuation (2.1%). CONCLUSION: We present the largest cohort that has monitored CK levels in a real-life setting, finding them elevated in 28.4% of patients. More research and monitoring will help us understand the clinical implications and the pathophysiological mechanism of CK elevation in this population.